Swarm Trajectories Generation for Target Capturing With Uncertain Information - Fedele, Giuseppe; D'Alfonso, Luigi; Bono, Antonio; Gazi, Veysel (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2023)
This work describes a methodology to generate trajectories for a swarm of agents, modeled as single integrators, for achieving target capturing/enclosing and containment. The discussed method proposes a robust solution that relaxes the strong assumptions about the exact knowledge of the target information. In particular, each agent requires a rough estimation of the reference, with a priori known bounded error both on the position and the velocity. It is shown that the swarm can be properly guided to enter a given capturing region while remaining outside a defined distancing region around the target. A steady-state analysis for velocity consensus is also provided for the case in which the reference information is exactly known by the agents.
Keywords: Uncertainty; Aerospace electronics; Target tracking; Space vehicles; Sensors; Robot sensing systems; Estimation; Distributed control; multiagent system; target capturing; target enclosing; target surrounding; NONHOLONOMIC MOBILE ROBOTS; COOPERATIVE CONTROL; CIRCUMNAVIGATION; LOCALIZATION; Automation & Control Systems; Computer Science